Embedded controller hardware design - Arnold, Ken, 1958- (Eagle Rock, VA : LLH Technology Pub., 2001)
Ken Arnold is an experienced embedded systems designer and president of HiTech Equipment, Inc., an embedded systems design firm located in San Diego, California. He also teaches courses in embedded hardware and software design at the University of California-San Diego. Gives the reader an integrated hardware/software approach to embedded controller design Stresses a "worst case" design approach for the harsh environments in which embedded systems are often used Includes design examples to make important concepts come alive.
Review of electronics fundamentals -- Microcontroller concepts -- Worst-case timing, loading, analysis, and design -- Memory technologies and interfacing -- CPU bus interface and timing -- A detailed design example -- Programmable logic devices -- Basic I/O interfaces -- Other interfaces and bus cycles -- Other useful stuff -- Other interfaces.
Includes index.
Keywords: Embedded computer systems -- Design and construction; Microprocessors; Computer input-output equipment; Computer engineering; Electronic books